BUSINESS ETHICS IN THE LIGHT OF THE PHILOSOPHY OF ETHICS - Anggraini, Rizky Maudy; Pradana, Hendra; Syarifuddin, Syarifuddin (Proceeding International Conference Keputeraan Prof. H. Kadirun Yahya; Vol 1 No 1 (2022): 1st International Conference Keputeraan Prof. Kadirun Yahya, 2022)
This research is about business ethics in the review of the philosophy of ethics, how the basic concept of business philosophy, how business ethics against the philosophy of ethics, and how the analysis of business ethics against the philosophy of ethics. In general, it is classified into two types, the first is descriptive ethics which emphasises the study of moral teachings that apply, discussing the problem of good and bad, human actions in living together. Secondly, normative ethics studies the teaching of good and bad norms as facts, there is no need to propose rational reasons for the teaching, it is enough to reflect on why it is a must. The theory of business ethics is teleology theory and deontology theory. Business ethics from the views of eastern philosophers, and western philosophers, as well as Islamic philosophers. Descriptive method with quantitative approach. This research has produced the conclusion that in the perspective of philosophy, ethics is understood as a philosophical reflection on morals, ethics is more of a normative discourse, but it does not always have to be imperative, because it can also be hypothetical, which talks about the conflict between good and bad, which is considered a relative value in the view of rational humans in acting. Ethics can also be seen as an art of living that leads to happiness and culminates in wisdom. While in the perspective of Islamic philosophy, ethics is loaded with theological content, the value of goodness based on the Qur'an and sunnah.